UJI ADAPTASI VARIETAS PADI LOKAL JAMBI DAN PADI UNGGUL NASIONAL DENGAN PEMBERIAN AMELIORAN PADA LAHAN RAWA PASANG SURUT SULFAT MASAM - Hadison, Abdul (Akta Agrosia, 2023)
Research on the adaptability of Jambi local rice and national rice varieties for cultivation under acid sulfate tidal swamp land with the application of ameliorants has been carried out in tidal swamp rice fields in Pembengis Village, Bram Hitam District, West Tanjung Jabung Regency, Jambi Province from April to September 2021.  Ten local and national rice varieties were evaluated, including Kuatik Tinggi, Kuatik Rendah, Karya Tinggi, Karya Rendah, Karang Duku, Bujang Berinai, Pandan Wangi, Padi Belanda, Inpara, and Inpari. Whereas, Ameliorant treatments consisted 4 kinds, namely without ameliorant (control), dolomite lime, rice husk ash and areca-nut-fiber ash.  The results of the experiment showed that there was an influence of local rice plant varieties on vegetative growth with the treatment of several rice plant varieties having a significant effect on rice plant height and significantly affecting panicle length, number of per panicle grain, and grain yield, but for the treatment parameters the maximum number of tillers and the number of productive tillers has no significant effect. Addition of ameliorants: dolomite lime, rice husk ash and areca nut fiber ash) showed reduction on rice plant height, maximum number of tillers, number of productive tillers, panicle length, number of grains per panicle, number of grains without panicles and grain yield. Keywords: adaptation test, local rice, jambi, ameliorant, swampland